Coccolithophore responses to the Pacific Decadal Oscillation in the East China Sea region of the Northwest Pacific from ad 1901 to 2013. (12th July 2019) - Yang, Shu; Yuan, Mingli; Yang, Qian; Huang, Jiansheng; Sun, Mengran; Sun, Jun; Qu, Keming; Sun, Yao
ABSTRACT: A high‐resolution study of coccolithophores in a sediment core from the East China Sea (ECS) region of the Northwest Pacific revealed that fluctuations in coccolithophore assemblages responded well to the Pacific Decadal Oscillation (PDO) during 1901–2013. Emiliania huxleyi and Gephyrocapsa oceanica were the most dominant species, accounting for more than 97% of all the ten detected species. The variation of the two dominant species showed a significant positive correlation, and they both increased during peak values of the PDO. Decreased stratification and increased nutrient supplementation from the bottom water induced by lower sea surface temperatures in the ECS, which were associated with high PDO values, were responsible for the dominant coccolithophore increase. Similarly, the increase of Calcidiscus leptoporus also corresponded to low‐temperature and high‐nutrient conditions associated with the cold phase in the ECS (positive phase of the PDO). The responses of decadal C. leptoporus variations to changes in cold and warm phases of the PDO in the Northwest and Northeast Pacific indicate that C. leptoporus preserved in sediment cores represents a potential indicator for reconstructing phase changes of the PDO during ancient times.